Induksi Kalus Kenerak (Goniothalamus umbrosus) Berdasarkan Jenis Eksplan Menggunakan Metode In Vitro - Mahadi, Imam (Jurnal Agro Teknologi Tropika, 2012)
A research on callus induction of kenerak (Goniothalamus umbrosus) from seed, leaf, stem and root explant wasconducted. Results showed that, seeds explant is the best on callus initiation using MS D10 (5,0 mg/l 2,4-D + 0,1 mg/lBAP) medium after 24 weeks cultured in light. However, mosf of all explants from leaves, stem and root formed callus onMS E8 ((3,0 mg/l 2,4-D + 0,5 mg/l BAP) and E10 ((5,0 mg/l 2,4-D + 0,5 mg/l BAP) medium after 2-6 weeks cultured inlight, respectively. Meanwhile for optimum callus proliferation, the suggessted medium was MS E10 ((5,0 mg/l 2,4-D +0,5 mg/l BAP).Therefore, in vitro technique can be used to produce callus of kenerak.